Project Completion Report of Index-Based Agriculture Insurance in Haor Area - Amarnath, Giriraj; Ahmed, Syed Moinuddin; Pavez, Ali T. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Several integrated plans and activities have been going on for a while now, at the direction of Honorable Prime Minister Sheikh Hasina of the Government of the People's Republic of Bangladesh under the supervision of the Financial Institutions Department of the Ministry of Finance to stand by the farmers who are at risk of financial loss in flood-prone Haor areas. To transform these plans into reality, with the extensive support from Insurance Development and Regulatory Authority of Bangladesh (IDRA), Green Delta Insurance Company Limited and its distribution channel partner OXFAM Bangladesh and local associate Sancred Welfare Foundation (SWF) have insured 316 Farmers of Tahirpur, Sunamganj area under Index-Based Crop Insurance as a pilot basis. Shadharan Bima Corporation has also piloted a project in Mithamoin Haor area to complement the pilot initiative and as per direction from the authorities. After almost a month of running this pilot, monitoring-updating-analyzing satellite and ground level data, Green Delta paid a claim of BDT 150,000 to 316 Boro Rice farmers, which GDIC considers as their success of this pilot phase. GDIC also suggests to replicate the pilot and carry out the success throughout the country while implementing Index-Based Crop Insurance in naturally vulnerable and mostly exposed areas of Bangladesh to strengthen the financial stability of farmers and increase the contribution of agriculture in the economy and national income. To implement Index Based Crop Insurance across the country the government needs to develop a number of high end technology and infrastructure to support them. Satellite remote sensing, real time data provider weather stations, digitalization of transaction methods, utilizing local authorities as structural distribution channel etc. are the most important initiatives that needs to be undertaken besides building stronger collaborations between respective departments and ministries of the government to get the most out this project.